2009
DOI: 10.4269/ajtmh.2009.81.296
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Antimicrobial Drug Resistance of Diarrheagenic Escherichia coli in Infants in Peru

Abstract: In a prospective passive diarrhea surveillance cohort study of 1,034 infants of low socioeconomic communities in Lima, Peru, we determined the prevalence and antimicrobial drug susceptibility of the diarrheagenic Escherichia coli . The prevalence of diarrheagenic E. coli was 29% (161 of 557) in children with gastroenteritis and 30% (58 of 195) in the control group without diarrhea. The most common E. coli pathogens in diarrhea were enteroaggregative E. coli (EAEC) (14%), enteropathogenic E. coli (EPEC) (7%), d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
82
7
24

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 34 publications
23
82
7
24
Order By: Relevance
“…Another report from northern Iran (2014) showed that 79.4% of the isolated E. coli were resistant to cefixime (30). Studies from Peru, Vietnam, Brazil and Mexico have also reported greater resistance to ampicillin in E. coli (31)(32)(33)(34). Our findings are similar to those of the studies from Iran, Peru, Vietnam, Brazil and Mexico (29)(30)(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Another report from northern Iran (2014) showed that 79.4% of the isolated E. coli were resistant to cefixime (30). Studies from Peru, Vietnam, Brazil and Mexico have also reported greater resistance to ampicillin in E. coli (31)(32)(33)(34). Our findings are similar to those of the studies from Iran, Peru, Vietnam, Brazil and Mexico (29)(30)(31)(32)(33)(34).…”
Section: Discussionsupporting
confidence: 82%
“…Studies from Peru, Vietnam, Brazil and Mexico have also reported greater resistance to ampicillin in E. coli (31)(32)(33)(34). Our findings are similar to those of the studies from Iran, Peru, Vietnam, Brazil and Mexico (29)(30)(31)(32)(33)(34). It should be also noted that in many cases, antibiotic resistance is transmitted to humans, hospitalized patients and the hospital environment through other sources, including food plants, animals, fish, poultries, and other industries, in which antibiotics are used for different purposes and may lead to the emergence of resistant strains (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, to date no clinical resistance breakpoint has been established for the members of the Enterobacteriaceae family by either CLSI or EUCAST (CLSI, 2013;EUCAST, 2015). However, the isolation of highly azithromycin-resistant Enterobacteriaceae is increasing worldwide and the emergence of azithromycin-resistance has been observed among different members of this family in different geographical areas (Baker et al, 2015;Boumghar-Bourtchai et al, 2008;Bowen et al, 2015;Le Hello et al, 2013;Ochoa et al, 2009;Sj€ olund Karlsson et al, 2013;Vlieghe et al, 2012).…”
Section: Mechanisms Of Resistancementioning
confidence: 99%
“…However, antimicrobial therapy is recommended for severely ill patients and for those with risk factors for invasive infection after obtaining appropriate blood and fecal cultures [2]. High frequency of resistance to antimicrobial agents among DEC isolated from children with diarrhea has been reported from several developing countries [3,4]. With the exception of ETEC [5], there little information published on the susceptibility of DEC from Egypt to antibiotics.…”
Section: Introductionmentioning
confidence: 99%